TIC et enseignement de la Chimie : au-delà des discours, quels dispositifs d'enseignement pour quels apprentissages? - MARIE-THÉRÈSE SALIBA; NAIM OUAINI; JACQUES GINESTIÉ; PIERRE NONNON (Metaichmio Publications, 2012)
In this research we suggest to take advantage of the opportunities offered by the new information and communication technologies (NICT). This new techno-scientific process of investigation will be realized via a laboratory of CAE (Computer assisted experimentations) where the computer is the learning tool that seeks in real time concrete observations. Experimental know- how, and the using of abstract representations to solve problems. To do this, we have introduced innovated courses in Didactics based on ICT/CAE in our Masters programs in the Holy Spirit University of Kaslik (USEK). These courses are intended for initial and continuous training of our student-teachers in mathematics and science and technology. Subsequently, our student-teachers will use CAE with their students in high schools for teaching chemistry to test and validate the functional aspect of the environment CAE proposed. The educational validation of this paradigm will be based on the confrontation between a priori analysis and subsequent findings to measure the gap of understanding that students have acquired.